Lichenoid tattoo hypersensitivity. Issue 6113 (11th March 1978) - Taaffe, A; Knight, A G; Marks, R
Abstract : Four patients are described who developed granulomatous reactions in the red portions of their tattoos. Histopathological and immunofluorescence studies showed features of lichen planus. Mercury was identified in only one patient's lesion, and hypersensitivity to mercury was shown by patch testing in one other patient. Tattooing may provide a localised antigenic challenge resulting in spontaneously occurring lichen planus.